Ephedrine vs. phenylephrine effect on sublingual microcirculation in elderly patients undergoing laparoscopic rectal cancer surgery - Zhang, Yanbing; Jin, Limin; Liu, Huayue; Meng, Xiaowen; Ji, Fuhai (Frontiers in Medicine, 2022)
Background: The effects of anesthesia administration on sublingual microcirculation are unknown. It is unclear how sublingual microcirculation responds to ephedrine or phenylephrine administration. We hypothesized that microvascular perfusion is impaired under anesthesia. Methods: We randomly divided 100 elderly patients undergoing laparoscopic rectal cancer surgery into phenylephrine and ephedrine groups in a 1:1 ratio. Ephedrine or phenylephrine was administered when MAP was <80% for >1 min. The heart rate (HR) and mean arterial pressure (MAP) were recorded every 5 min. Lactic acid was tested both pre- and postoperatively. The sublingual microcirculation characteristics of the microvascular flow index, the percentage of perfused vessels, the density of perfused vessels, and the heterogeneity index were monitored using a sidestream dark field imaging device. Results: Their MAP showed an evident decrease of >20%. At this point, the HR, microvascular flow index, perfused vessel density, and proportion of perfused vessels decreased similarly in ephedrine and phenylephrine groups. Conversely, the heterogeneity index increased in both groups. After phenylephrine and ephedrine administration, ephedrine treatment significantly increased the proportion of perfused vessels, microvascular flow index, and HR compared with phenylephrine treatment. Conclusion: General anesthesia was associated with reduced MAP, HR, and sublingual microcirculation in elderly patients undergoing laparoscopic rectal cancer surgery. The results of ephedrine treatment were better than those of phenylephrine treatment in terms of HR, increased the proportion of perfused vessels, and microvascular flow index of sublingual microcirculation. Trial Registration: Chinese Clinical Trial Registry (identifier: ChiCTR-2000035959).